2010
DOI: 10.1128/jb.00700-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lipid Export in Hydrocarbonoclastic Bacteria of the GenusAlcanivorax: Identification of Lipid Export-Negative Mutants ofAlcanivorax borkumensisSK2 andAlcanivorax jadensisT9

Abstract: Triacylglycerols (TAGs), wax esters (WEs), and polyhydroxyalkanoates (PHAs) are the major hydrophobic compounds synthesized in bacteria and deposited as cytoplasmic inclusion bodies when cells are cultivated under imbalanced growth conditions. The intracellular occurrence of these compounds causes high costs for downstream processing. Alcanivorax species are able to produce extracellular lipids when the cells are cultivated on hexadecane or pyruvate as the sole carbon source. In this study, we developed a scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Use of hydrocarbonoclastic bacteria (HCB) to produce lipophilic substances like PHA, TAG, or WE as bulk chemicals from hydrocarbons, was recently reviewed [7]. Alcanivorax borkumensis SK2 seems to be particularly feasible for production of neutral lipids, because this bacterium is also able to export and deposit in the medium the produced neutral lipids like TAG or WE [8]. The latter may be important if the neutral lipids are produced biotechnologically.…”
Section: Introductionmentioning
confidence: 98%
“…Use of hydrocarbonoclastic bacteria (HCB) to produce lipophilic substances like PHA, TAG, or WE as bulk chemicals from hydrocarbons, was recently reviewed [7]. Alcanivorax borkumensis SK2 seems to be particularly feasible for production of neutral lipids, because this bacterium is also able to export and deposit in the medium the produced neutral lipids like TAG or WE [8]. The latter may be important if the neutral lipids are produced biotechnologically.…”
Section: Introductionmentioning
confidence: 98%
“…As mentioned above, A. borkumensis SK2 is able to produce and accumulate TAGs as the main storage compound when it is cultivated in the presence of pyruvate as the sole carbon source. Although the export of TAGs has been reported recently (31), in this study we analyzed only the intracellular accumulation of TAGs in order to establish the function of these compounds in A. borkumensis SK2. Recently, it was demonstrated that the amount of accumulated TAGs in this strain diminishes if at least one of the two WS/DGAT (Fig.…”
Section: Borkumensis Mutant Defective In Lipid Biosynthesis 2887mentioning
confidence: 99%
“…In Acinetobacter species, WEs are degraded into water-soluble molecules and CO 2 during carbon starvation, thereby demonstrating that they serve as an ATP-generating substrate during starvation (16). Accumulation of WEs in species of the genus Acinetobacter (16) but also in marine bacteria such as Marinobacter (25) and Alcanivorax (10,28,31) species has been described previously. Also, marine hydrocarbonoclastic bacteria of the genus Alcanivorax are able to export lipids such as TAGs and WEs (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the localization of neutral lipids in organisms is not restricted to the cell cytoplasm, as extracellular lipid deposition has been shown in various strains. There are many strains of bacteria presenting the ability of extracellular TAGs production, like Alcanivorax, 90 Acinetobacter, 91 Alcaligenes and Pseudomonas. 92 It was also reported that similar secretion of fatty acids or TAGs can be achieved by metabolic engineering and mutagenesis, not only in bacterium E. coli, but also in some yeast strains and microalgae.…”
Section: Genetic Engineering For Extracellular Secretion Of Lipophilimentioning
confidence: 99%